Role Rattan Industry Subsector analysis of the Economy of Palangka Raya City - Trisna, Ayu; Siagian, Washington; Takari, Dedi (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2018)
The purpose of this study was to analyze the basic sectors in Palangka Raya City, to analyze the role of the rattan handicraft industry on the economy of Palangka Raya City, and to analyze the conditions of the factors (capital, labor, government regulations for production and market access) that support and develop the rattan handicraft industry in Palangka Raya City. The analytical method used in this study is the Location Quotiation (LQ) analysis and Shift Share (SS) analysis. The data used are primary data (in the form of interviews and giving questionnaires to rattan craftsmen, rattan consumers and government agencies related to the development of rattan) and secondary data (in the form of GDP, economic growth in Central Kalimantan in 2010-2014, and the development of the 2010-2014 small and medium rattan handicraft industry in the City of Palangka Raya). The results of the study show that the manufacturing sector is a non-base sector in the City of Palangka Raya. The small and medium industry sector of rattan handicrafts has a very good role in the growth of rapid employment and is included in the progressive group, but has not been able to compete with other industrial sub-sectors in other regions in the Palangka Raya City area. In addition, based on the results of the study also stated that various efforts and policies have been carried out by the Central Kalimantan Regional Government to support the development and advancement of the small and medium-sized industrial sector of rattan handicrafts, namely (1) Using rattan meubel / furniture for other office equipment, (2) Using products rattan bags or other combinations for education and training purposes, (3) Using rattan products (such as tissue boxes, trash baskets, fruit baskets etc.), (4) Helping promote rattan-based products to guests / tourists who come to Palangka Raya, ( 5) Budgeting the cost of purchasing rattan-based products either through the regional income and expenditure budget / state budget and expenditure on each company's budget, (6) Hold exhibitions inside and outside Palangka Raya.